2006
DOI: 10.1097/01.gme.0000168061.32917.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aromatase inhibition on sexual function and well-being in postmenopausal women treated with testosterone: a randomized, placebo-controlled trial

Abstract: Increases in total and free T in the physiologic range in postmenopausal women were associated with improved sexual satisfaction, well-being, and mood. In this study, aromatase inhibition did not influence any of these outcomes. Short-term transdermal T therapy did not modify fasting lipids, lipoprotein(a), or C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 27 publications
1
59
1
2
Order By: Relevance
“…Blood levels of both testosterone and DHT remained suppressed in women throughout all three hormone conditions in which DISF scores were reduced relative to baseline. Blood testosterone levels were decreased by approximately 30% during Lupron-induced hypogonadism compared with baseline and, therefore, changes in testosterone (or one of its androgen or neurosteroid metabolites) could mediate the observed decline in sexual function and quality of orgasm in women Sherwin et al, 1985;Lobo et al, 2003;Nathorst-Boos et al, 2006;Braunstein et al, 2005;Sherwin and Gelfand, 1987;Shifren et al, 2000;Floter et al, 2002;Davis et al, 2006;Leiblum et al, 2006;Santoro et al, 2005). However, since testosterone was not administered to women in this study, we only can speculate about this possible relationship.…”
Section: Discussionmentioning
confidence: 51%
“…Blood levels of both testosterone and DHT remained suppressed in women throughout all three hormone conditions in which DISF scores were reduced relative to baseline. Blood testosterone levels were decreased by approximately 30% during Lupron-induced hypogonadism compared with baseline and, therefore, changes in testosterone (or one of its androgen or neurosteroid metabolites) could mediate the observed decline in sexual function and quality of orgasm in women Sherwin et al, 1985;Lobo et al, 2003;Nathorst-Boos et al, 2006;Braunstein et al, 2005;Sherwin and Gelfand, 1987;Shifren et al, 2000;Floter et al, 2002;Davis et al, 2006;Leiblum et al, 2006;Santoro et al, 2005). However, since testosterone was not administered to women in this study, we only can speculate about this possible relationship.…”
Section: Discussionmentioning
confidence: 51%
“…Also, since T binds to SHBG more avidly than does E 2 , it is conceivable that raising the circulating concentrations of androgens would displace E 2 from SHBG. However, as noted above in the transdermal T studies, there was no elevation in either the total or free E 2 levels after T administration compared with the baseline values (36,(38)(39)(40)(41)(42).…”
Section: Breast Cancermentioning
confidence: 63%
“…However, studies have shown that aromatase activity in breast cancer tissue is inversely related to the estrogen status of the womenthose with low serum estrogen concentrations have higher aromatase activity, while women receiving estrogens have lower aromatase activity, which suggests that androgen administration given on a background of concomitant estrogen treatment is unlikely to result in much local biotransformation to estrogens (124)(125)(126)(127)(128). Additionally, in the transdermal T patch and gel studies, the mean serum estradiol level following testosterone administration averaged 104% of the baseline, with a range of 79%-125% in the various studies (34)(35)(36)(38)(39)(40)(41)(42)(43)(44). Following the intramuscular administration of testosterone esters in female-to-male transsexuals, the average serum estradiol level was 99.2% of the baseline, with a range of 96%-113% (56,57).…”
Section: Breast Cancermentioning
confidence: 92%
“…It seems that androgens exhibit a promoting effect on behavior and mood, whereas in elderly women, free testosterone levels correlate inversely to symptoms of depression (108). Physical and cognitive function seem to be improved in postmenopausal women with elevated circulating testosterone levels (107,109,110).…”
Section: Sequelsmentioning
confidence: 99%